Pengaruh ekspor, utang luar negeri, neraca transaksi berjalan dan neraca transaksi modal terhadap cadangan devisa di Indonesia - Graselita Aritonang; Amril Amril; Zulgani Zulgani (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
The purpose of this study is to (1) see the description of Indonesia's foreign exchange reserves, exports, foreign debt, current account balance, and capital account balance for the period 1998-2017. (2) analyze the effect of exports, foreign debt, current account balance, and capital account balance on Indonesia's foreign exchange reserves. The method used in this research is quantitative descriptive analysis with multiple regression model analysis using the Ordinary Least Square (OLS) method. The results of this study show that the average development of Indonesia's foreign exchange reserves is 11.87 percent, exports are 7.38 percent, foreign debt is 4.51 percent, the current account balance is 514.89 percent and the capital account balance is 66.92 percent. Based on the results of the analysis carried out by exports, foreign debt, current account balance, and capital account have a positive and significant effect on foreign exchange reserves with a coefficient of determination of 98.37 percent. Keywords: Foreign exchange, export, Foreign debt, Current account, Capital account